Cognitive Impairment in Frail Hypertensive Elderly Patients: Role of Hyperglycemia - Pasquale Mone; Jessica Gambardella; Antonella Pansini; Antonio de Donato; Giuseppe Martinelli; Eugenio Boccalone; Alessandro Matarese; Salvatore Frullone; Gaetano Santulli (Cells, 2021)
Endothelial dysfunction is a key hallmark of hypertension, which is a leading risk factor for cognitive decline in older adults with or without frailty. Similarly, hyperglycemia is known to impair endothelial function and is a predictor of severe cardiovascular outcomes, independent of the presence of diabetes. On these grounds, we designed a study to assess the effects of high-glucose and metformin on brain microvascular endothelial cells (ECs) and on cognitive impairment in frail hypertensive patients. We tested the effects of metformin on high-glucose-induced cell death, cell permeability, and generation of reactive oxygen species in vitro, in human brain microvascular ECs. To investigate the consequences of hyperglycemia and metformin in the clinical scenario, we recruited frail hypertensive patients and we evaluated their Montreal Cognitive Assessment (MoCA) scores, comparing them according to the glycemic status (normoglycemic vs. hyperglycemic) and the use of metformin. We enrolled 376 patients, of which 209 successfully completed the study. We observed a significant correlation between MoCA score and glycemia. We found that hyperglycemic patients treated with metformin had a significantly better MoCA score than hyperglycemic patients treated with insulin (18.32 ± 3.9 vs. 14.94 ± 3.8; p < 0.001). Our in vitro assays confirmed the beneficial effects of metformin on human brain microvascular ECs. To our knowledge, this is the first study correlating MoCA score and glycemia in frail and hypertensive older adults, showing that hyperglycemia aggravates cognitive impairment.